2012
DOI: 10.1007/s12020-012-9806-9
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary metastasis of thyroid cancer

Abstract: Pituitary metastases (PM) from thyroid cancer are rare, but their management can represent a difficult challenge for the endocrinologist. Our aim was to review all reported cases of PM from thyroid cancer. PubMed was consulted and 19 papers reporting 20 cases were found. We moreover discuss two of our own cases, which had come to our attention within a few months of one another. Eleven cases were follicular cancer, eight cases were papillary cancer, two cases were medullary cancer, and one case was an insular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…The frequencies of primary sites are summarized in Fig. 1 (10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 10...…”
Section: Resultsmentioning
confidence: 99%
“…The frequencies of primary sites are summarized in Fig. 1 (10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 10...…”
Section: Resultsmentioning
confidence: 99%
“…First presentation of thyroid malignancy with visual symptoms from SSR metastasis, as in our patient, is a rare but well described feature. In a review of 22 cases of pituitary metastasis from thyroid cancer, Barbaro et al reported pituitary metastasis to be the first presentation in nine patients (9/22, 40%) (29). Another peculiar feature in our patient was the absence of DI.…”
Section: Sellar Metastasismentioning
confidence: 46%
“…At least in part the reason is that these two types of malignancies are most commonly encountered in clinical practice. Less often described are metastasis of renal cell carcinoma, gastrointestinal tumours, lymphomas, leukemias, thyroid carcinomas, myeloma, hepatocellular carcinoma and rhabdomyosarcoma (Table 1) [1,2,[7][8][9][10][11][12][13][14][15][16][17][18][19]. When confirming the metastasis in the pituitary, there are frequently metastases present at several other locations, most often in bones.…”
Section: Discussionmentioning
confidence: 99%